2017
DOI: 10.1016/j.ajog.2017.04.007
|View full text |Cite
|
Sign up to set email alerts
|

Racial and ethnic differences in the prevalence of metabolic syndrome and its components of metabolic syndrome in women with polycystic ovary syndrome: a regional cross-sectional study

Abstract: Despite a unifying diagnosis of polycystic ovary syndrome, there are significant differences in the prevalence of metabolic syndrome and clustering of its components based on race and ethnicity, which may reflect contributions from both racial and environmental factors. Our findings indicate the prevalence of metabolic syndrome components varies in women with polycystic ovary syndrome, such that compared to White women from the United States, Black US women had the highest prevalence, whereas women from India … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

3
52
0
5

Year Published

2017
2017
2023
2023

Publication Types

Select...
6
1

Relationship

0
7

Authors

Journals

citations
Cited by 72 publications
(60 citation statements)
references
References 42 publications
3
52
0
5
Order By: Relevance
“…Additionally, in a separate meta-analysis it was found that soy isoflavone consumption significantly correlated with reduced body weight, glucose and insulin levels in non-Asian postmenopausal women [45]. High levels of dietary phytoestrogen consumption in Asian populations may explain the reduced incidence of metabolic syndrome [46]. Further characterization of this consequence may prove to be a useful therapeutic tool in combating postmenopausal-induced metabolic syndrome.…”
Section: Obesity and Metabolic Syndromementioning
confidence: 98%
See 1 more Smart Citation
“…Additionally, in a separate meta-analysis it was found that soy isoflavone consumption significantly correlated with reduced body weight, glucose and insulin levels in non-Asian postmenopausal women [45]. High levels of dietary phytoestrogen consumption in Asian populations may explain the reduced incidence of metabolic syndrome [46]. Further characterization of this consequence may prove to be a useful therapeutic tool in combating postmenopausal-induced metabolic syndrome.…”
Section: Obesity and Metabolic Syndromementioning
confidence: 98%
“…Polycystic Ovary Syndrome (PCOS) patients have an increased incidence of metabolic syndrome, however, this incidence is not uniform across women from different countries and of varying ethnicity [46]. PCOS is a hyperandrogen and low estrogen driven disease, and patients suffering from PCOS have significantly lower gut microbiota diversity compared to healthy controls [39,54].…”
Section: Polycystic Ovary Syndromementioning
confidence: 99%
“…Astonishingly, BMI, WC, and the 10-year CVD risk score did not significantly differ between the studied populations. Chan et al in a cross-sectional study found that black women from the United States had over 4 times higher odds of the prevalence of MetS than US white women after age adjustment 122. However, hypertriglyceridemia was found significantly less frequent in black women both by Chan et al122 and Engmann et al121 The knowledge of the prevalence of MetS in different races and ethnicities in PCOS women may help in targeting the populations for early screening, prevention, or treatment and to identify specific goals of intervention.…”
mentioning
confidence: 99%
“…Chan et al in a cross-sectional study found that black women from the United States had over 4 times higher odds of the prevalence of MetS than US white women after age adjustment 122. However, hypertriglyceridemia was found significantly less frequent in black women both by Chan et al122 and Engmann et al121 The knowledge of the prevalence of MetS in different races and ethnicities in PCOS women may help in targeting the populations for early screening, prevention, or treatment and to identify specific goals of intervention. The diversity of the medication use, especially treatment with oral contraceptives or metformin, also was a potential confounding factor.Other methodological weaknesses of the cited publications were imprecise, different, or nonreported diagnostic criteria for abnormal glucose tolerance, AH, MetS, or obesity.…”
mentioning
confidence: 99%
“…1 In 2003, the Rotterdam consensus proposed that PCOS could be diagnosed after excluding other causes of menstrual irregularity, the presence of ovary cysts, and hyperandrogenism, 2 and their healthcare providers must be aware of the possible risks and complications of PCOS including those related to the cardiovascular system, and endocrine, metabolic, and body composition parameters. [2][3][4][5][6] The cause and effect relationship between increased insulin resistance (IR) and excess testosterone is evident in PCOS. This has been associated with increased visceral fat and metabolic syndrome, [4][5][6][7] which predisposes to the development of metabolic chronic diseases 2,6,7 and of cardiovascular disorders that directly impair the physiology of normal heart function and are often accompanied by impairments in cardiac autonomic control.…”
Section: Introductionmentioning
confidence: 99%